Hydrotropic Solubilization: A Promising Approach for Enhancing the Solubility of Poorly Water-Soluble Drugs - R. Senthilkumar; R. Sridhar; G. Surendran; C. Jayakumar (Pharmaceutical Research: Recent Advances and Trends Vol. 5, 2024)
The solubilisation of poorly water-soluble drugs is a critical aspect of chemical screening and formulation research. Various techniques are employed to enhance the water solubility of such drugs, and among these techniques, hydrotropic solubilization is one of the most effective methods. Hydrotropes are compounds that help dissolve hydrophobic substances in aqueous solutions without causing problems related to emulsification, which is common in surfactant solutions. This method is highly suitable for industrial applications because solutes can be easily retrieved and hydrotrope solutions can be reused. Hydrotropes exhibit pH-independent solvent properties, and high selectivity, and are nonflammable, affordable, and easily obtainable. These factors make this technique superior to other solubilization methods. This study introduces hydrotropy, focusing on its generation, with a detailed account of various techniques for improving its solubility. Hydrotropic solubilisation is a viable and economically attractive strategy for enhancing the aqueous solubility of poorly water-soluble drugs, which is highly beneficial for pharmaceutical formulations and achieving recognition of its potential in the industry.